Efikasi Herbisida 2,4-Dimetil amina dan Glifosat dalam Pengendalian Gulma Pisang (Musa sp) di Perkebunan Kelapa Sawit - Sylvia Madusari (JURNAL CITRA WIDYA EDUKASI, 2018)
This study aims to determine the efficacy of herbicides 2,4-Dimethyl amine and Glyphosate to control weeds which is banana (Musa sp) in Palm Oil Plantation. The method used is the implant method by a bamboo punctured with a size of ± 30 cm. Use of 2,4-Dimethyl amine consists of three variations of a treatment that is 20 cc/liter, 40 cc/liter and 60 cc/liter, while Glyphosate applied at 50 cc/50 liters with three methods, namely with implant, injection and slash, each treatment consisted of three samples and each treatment consisted of two replicates. The results showed that the application of 2,4-Dimethyl amine with a water concentration of 20 cc/liter has a better control of the weed banana compared with a water concentration of 40 cc/liter and 60 cc/liter. In applications using Glyphosate, the implant method has a best method to control when compared to injectable application.